Assessing the attitudes and knowledge of medical students towards Patient-Centred Care across different study years: a cross-sectional study - Hamayal, Muhammad; Iftikhar, Iqra; Muhammad Danyal Tahir; Muhammad Bilal Nadeem; Warda Shahid; Altaf Hussain (Journal of the Pakistan Medical Association, 2024)
Objective: To determine how medical students viewed the importance of patient-doctor communication, to assess their knowledge about patient-centred care, and to compare the attitudes of medical students in their pre-clinical and clinical years of study towards patient-centred care. Method: The cross-sectional study was conducted from April to September 2023 at Federal Medical and Dental College, Islamabad, and Rawalpindi Medical University, Rawalpindi, Pakistan, and comprised medical students of either gender from 2nd to 5th academic year. Data was collected using the Patient-Practitioner Orientation Scale. Data was analysed using SPSS 27. Results: Of the 322 students, 178(55.3%) were males and 144(44.7%) were females. The mean score was 3.60±0.47, while the sharing and caring sub-scores were 3.23±0.66 and 3.99±0.52, respectively. The attitude of students overall was slightly patient-centred. Different study years showed variance in patient-centred scores which were also affected by cultural, demographic and gender parameters (p<0.05). Conclusion: The attitude of the students leaned slightly towards patient-oriented behaviour. Key Words: Patient-centred care, Physician-patient relations, Students, Medical, Patient satisfaction.